HUBUNGAN RESISTENSI INSULIN DENGAN KADAR NITRIC OXIDE PADA OBESITAS ABDOMINAL - Cahjono, Heru; Gde Budhiarta, Anak Agung (journal of internal medicine; Vol. 8, No. 1 Januari 2007, 2012)
Numerous studies that confirmed the important link between central obesity and endothelial dysfunction (ED) is further supported by the concept that insulin sensitivity is partly determined by the ability of endothelium to produce nitric oxide (NO). In this condition, HOMA-IR, the model which is a convenient means of evaluating insulin resistance has thus far been related to ED. Nitric oxide plays important physiological roles in the endothelium, where free radical NO is synthesized from the amino acid l-arginine by endothelial constitutive NO synthase (eNOS) and released. Endothelium-derived NO is a potent vasodilator as well as an inhibitor of platelet aggregation and adhesion, and is associated with the development of cardiovascular disease (CVD) in the presence of endothelial dysfunction (ED), which plays an early and prominent role in atherosclerotic plaque formation. We raised the question as to whether insulin resistance in the abdominal obesity group had association with NO levels contribute to affect endothelial dysfuntion. Cross sectional study had been conducted during January until March 2007. The study involved 67 employees at Sanglah Hospital with abdominal obesity using criteria for Asian people (male WC 90 cm; female WC 80 cm). Serum concentrations of NO metabolites were evaluated through the measurement of metabolic end products, ie, nitrite and nitrate, using enzymatic catalysis coupled with Griess reaction, Serum concentration of insulin was measured by immunoassay method. Plasma glucose, cholesterol, HDL-cholesterol, LDL-cholesterol and triglicerydes were determined by enzymatic procedure after overnight fast. The study involved 45 female and 25 male subjects, 23-56 years of age. Insulin resistance had association with waist circumference (r=0,511; p <0,01) and there was no association between insulin resistance and NO titer (r=0,054; p<0,664) but after adjusted with ESR 20-30 mm/h r=-0,486; p<0,048. However, serum concentrations of NO did not have association with component of metabolic syndrome and neither did insulin resistance. The present data indicate there is no association between insulin resistance and NO levels except for ESR 20-30 mm/h. This possibility is due to low grade chronic inflammation role on the pathogenesis of endothelial dysfunction in obesity
Keywords: NO, obesity, insulin resistance